2021
DOI: 10.34133/2021/5612850
|View full text |Cite
|
Sign up to set email alerts
|

Kilometers Long Graphene-Coated Optical Fibers for Fast Thermal Sensing

Abstract: The combination of optical fiber with graphene has greatly expanded the application regimes of fiber optics, from dynamic optical control and ultrafast pulse generation to high precision sensing. However, limited by fabrication, previous graphene-fiber samples are typically limited in the micrometer to centimeter scale, which cannot take the inherent advantage of optical fibers—long-distance optical transmission. Here, we demonstrate kilometers long graphene-coated optical fiber (GCF) based on industrial graph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…chemical activity (e.g., for adsorption of gas molecules) [199] and a strong enhancement of the device's optical response, [200,201] thus leading to advanced photo-physical and photo-biochemical sensors with combined high selectivity and sensitivity on versatile photonic platforms ranging from fibers and waveguides to interferometers and microresonators. [202][203][204][205] For instance, the intense third order nonlinear optical response of graphene integrated on microcavities (Figure 9a) and fibers (Figure 9b) has been exploited for sensing applications using either the stimulated Brillouin optomechanical response or the FWM process. [3,206] In a graphene based Brillouin optomechanical microresonator, when the phase matching condition k p = k s + k A , where k i is the momentum of the pump (p), signal (s), and acoustic (A) wave, is fulfilled a new field at the pump-signal difference frequency in the ≈10 2 MHz domain is excited.…”
Section: Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…chemical activity (e.g., for adsorption of gas molecules) [199] and a strong enhancement of the device's optical response, [200,201] thus leading to advanced photo-physical and photo-biochemical sensors with combined high selectivity and sensitivity on versatile photonic platforms ranging from fibers and waveguides to interferometers and microresonators. [202][203][204][205] For instance, the intense third order nonlinear optical response of graphene integrated on microcavities (Figure 9a) and fibers (Figure 9b) has been exploited for sensing applications using either the stimulated Brillouin optomechanical response or the FWM process. [3,206] In a graphene based Brillouin optomechanical microresonator, when the phase matching condition k p = k s + k A , where k i is the momentum of the pump (p), signal (s), and acoustic (A) wave, is fulfilled a new field at the pump-signal difference frequency in the ≈10 2 MHz domain is excited.…”
Section: Sensingmentioning
confidence: 99%
“…[ 6,195–198 ] In most cases, 2D materials provide both the chemical activity (e.g., for adsorption of gas molecules) [ 199 ] and a strong enhancement of the device's optical response, [ 200,201 ] thus leading to advanced photo‐physical and photo‐biochemical sensors with combined high selectivity and sensitivity on versatile photonic platforms ranging from fibers and waveguides to interferometers and microresonators. [ 202–205 ]…”
Section: Sensingmentioning
confidence: 99%
“…These fibres are also more thermally conductive, which could be exploited for fast thermal sensing [13], and the increased Young's modulus of the NC coating layers should influence e.g., vibration behaviour of the fibres. All these potential properties can be harnessed to improve the sensing performance of conventional polyimide-coated fibres.…”
Section: Outlook and Future Workmentioning
confidence: 99%
“…To fully unlock the potential of NC-coated optical fibres for distributed fibre sensing applications and show their commercial relevance, access to kilometre lengths of these fibres with uniform coatings are required. A continuous process for coating long lengths of optical fibres with a mixture of graphene-acrylate (30%-wt) was reported [13], using jet spray. The authors reported that, when used as temperature sensors, these fibres demonstrated fast thermal response, with thermal diffusivity 30-fold higher in the axial direction than a conventional acrylate coated silica fibre.…”
Section: Introductionmentioning
confidence: 99%
“…High-polymer flexible materials may struggle to sustain their long-term stability in complex environments. There are many hybrid material-based fiber sensors such as those incorporating graphene 9 and silica, 10 which are also known to withstand high temperatures. We can also protect internal sensors by wrapping them in a heat-resistant dielectric layer.…”
Section: Introductionmentioning
confidence: 99%